A Review on Task Scheduling Approaches Based on Weighted Round Robin Algorithm in Cloud Environment - Noortaj, S; Venkataramana, K (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing uses the concepts of scheduling and load balancing to move around tasks to underutilized VMs for effectively sharing the resources. The scheduling of the tasks in the cloud computing environment is an irrecoverable restraint and hence it has to be assigned to the most appropriate VMs at the initial placement itself. Practically, the arrived jobs consist of multiple tasks and they may execute the tasks in multiple VMs or in the same VM’s multiple cores. Also, the jobs arrive during the run time of the server in changeable random intervals under various load conditions. The participating various resources are managed by allocating the tasks to appropriate resources by static or dynamic scheduling to make the cloud computing more efficient and thus it improves the user satisfaction. Objective of this work is to introduce and evaluate the proposed scheduling and load balancing algorithm by considering the capability of each virtual machine (VM), the task length of each requested job, and the of multiple tasks. Performance of the proposed algorithm is studied by comparing with the accessible methods.